????? ??????? ??? ??????? ?????????? ????? ??????? ??? ?????? ????? ??????? - Abdullah Mama (El-Tsaqafah : Jurnal Jurusan PBA, 2020)
This research aims to explain the government’s policy and thestatus of scholars in southern Thailand and their efforts in disseminatingIslamic sciences, focusing on the efforts of devoted scholars in particular in adifferent field as well as focusing on the development and progress of Islamiceducation and reform in southern Thailand, which the government decideswith political and economic factors, the higher the state of governmentintervention For the educational or educational system, it will be moreopen to the occurrence of Islamic educational and educational reform. Thisindicates that the government supports what we suggested and indicated,and also clarifies what officials have reached, positive or negative.Using primary sources as follows: 1. Islamic Council documents in the stateof Fatani and government education laws: 2. Public and private Islamicschools system: 3. Interview with leaders of Islamic education in southernThailand: 4. Interview with leaders of the General Education Departmentin Thailand, the research was milked with the curriculum Historical studyof the dynamics of Islamic education, while the political method is used toevaluate government policies and programs on Islamic education. ???? ??? ????? ??? ???? ????? ??????? ?????? ??????? ?????? ??????? ??????? ?? ??? ?????? ?????????? ????? ??? ???? ?????????? ???? ?? ???? ?????? ????? ??????? ??? ???? ????? ??????? ????????????????? ?? ???? ??????? ????? ?????? ??????? ???????? ???????????????????? ???? ?????? ???? ?????? ??????? ?????? ??????? ?? ?????????????? ??????? ????? ??????? ??????? ????????? ????????. ???? ??? ??? ?? ??????? ???? ???? ??????? ??????? ????? ????? ?? ????? ???? ??????????? ????? ????????? ?? ???????.????????? ??????? ??????? ??? ?????: 1.????? ?????? ???????? ??????????? ??????? ??????? ???????: 2.???? ??????? ????????? ???????? ???????:3.???????? ?? ???? ??????? ????????? ?? ???? ???????: 4.???????? ?? ???? ???????????? ????? ????????? ?? ????? ????? ??????? ???????? ?????? ???????? ????????????????? ?? ??? ??? ??????? ?????? ??????? ?????? ???????? ???????????????? ??? ??????? ????????.